The Transformation of Reference Services in Hamzah Sendut Library, Universiti Sains Malaysia. (15th June 2016) - Ahmat, Muhammad Akmal; Jaafar, Cik Ramlah Che; Azmi, Noor Adilah
Abstract: Beginning in the year 2008, Universiti Sains Malaysia (USM) is fortunate to be selected to lead the Accelerated Program for Excellence (APEX) and Research University (RU) agenda. Hence, the USM Hamzah Sendut Library, through reference librarians had to strengthen the public services especially in facilitating the reference services for customers. Since then, reference librarians assigned to Reference and Research Division (RRD), have had to take the challenge to change the traditional services and expect the transference on customer demands. The reference librarians have to review the quality of current reference services and explore additional services that meet the customers' expectation for long period. This study aims to discover the reference services trend at RRD, after the APEX agenda was implemented. The study also investigates whether the services provided fulfill the requirements of the customers. Next, the study also aims to identify the additional services that could be implemented in RRD. The study collected and analyzed the reference enquiries retrieved from the library system within 6 years of APEX establishment. The reference enquiries were based on the interview conducted between RRD librarians and the customers. The main focus of the analysis was the types of customer questions to search the key necessity of customers' needs. Based on that, the important components of customer demand were identified. After that, Blue Ocean Strategies (BOS) was applied to identify the additional services needed in USM's Library. The findings revealed that the trend on customer demands for reference services evolved into various patterns. This study shows that the reference librarians need to stay alert on the changing trend and prepare to reform the services accordingly in order to sustain customer trust and expectations on the reference services.